KUALITAS PAPAN KOMPOSIT BERLAPIS FINIR DARI SABUT KELAPA DAN PLASTIK POLIETILENA DAUR ULANG: VARIASI UKURAN PARTIKEL SABUT KELAPA - Dina Setyawati; Yusuf Sudo Hadi; Muh. Yusram Massijaya; Naresworo Nugroho (Forestry Faculty of Universitas Hasanuddin, 2006)
Agricultural fibers are currently used as a substituted resource to wood-based products. One of agricultural fibers that has been developed and become a resource for panel products is coir (coconut fiber). The purpose of this study is to evaluate the quality of veneered composite board made of coir and recycled polyethylene (RPE). The target density of board samples was 0.7 g/cm3. The board construction type is core type composite board (three layers). Veneers from Meranti (Shorea sp.) were used as face and back layers and coir was in the core layer. RPE composition was 50% based on coir particle and veneers oven dry weights. Recycled plastics were placed in three layers, 30% on the face and back layers, and 70% in the core layer. The coir sizes were under 1 cm, 1 cm, 5 cm, 10 cm, and 10 cm up (along coir size). The composite board samples were tested by JIS A 5908 – 1994. Each parameter was measured in three replications. The research results obtained are as follows : (1) Veneered composite boards made of coir and RPE fulfill the JIS A 5908 standard in term of density, thickness swelling after 2 and 24 hours of water immersions, modulus of elasticity, modulus of rupture and internal bond, and (2) The coir size did not significantly affect the properties of composite board. Keywords: veneered composite board, coir size, recycled polyethylene